2011
DOI: 10.1186/1556-276x-6-356
|View full text |Cite
|
Sign up to set email alerts
|

Study on the visible-light-induced photokilling effect of nitrogen-doped TiO2 nanoparticles on cancer cells

Abstract: Nitrogen-doped TiO2 (N-TiO2) nanoparticles were prepared by calcining the anatase TiO2 nanoparticles under ammonia atmosphere. The N-TiO2 showed higher absorbance in the visible region than the pure TiO2. The cytotoxicity and visible-light-induced phototoxicity of the pure- and N-TiO2 were examined for three types of cancer cell lines. No significant cytotoxicity was detected. However, the visible-light-induced photokilling effects on cells were observed. The survival fraction of the cells decreased with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 23 publications
7
34
1
1
Order By: Relevance
“…Furthermore, in a previous study, the same group demonstrated that N-TiO 2 NPs are capable of inducing cytotoxicity and micronuclei formation in three cancer cell lines. 53 There are several notable differences between our study and the studies of Li. One such difference is the intensity and duration of light used among the studies.…”
contrasting
confidence: 49%
“…Furthermore, in a previous study, the same group demonstrated that N-TiO 2 NPs are capable of inducing cytotoxicity and micronuclei formation in three cancer cell lines. 53 There are several notable differences between our study and the studies of Li. One such difference is the intensity and duration of light used among the studies.…”
contrasting
confidence: 49%
“…Stefanous et al also indicated that photoexcited TiO 2 nanoparticles efficiently inhibited the aggregation of platelets, which led to discontinuation of haematogenous metastasis [8]. The photo-killing effect of nitrogen-doped TiO 2 nanoparticles in the visible region also has been reported [9].…”
Section: Introductionmentioning
confidence: 93%
“…The electrons in the valence band of TiO 2 can be excited to the conduction band by ultraviolet (UV) radiation with the wavelength shorter than 387 nm (corresponding to 3.2 eV as the band gap energy of anatase TiO 2 ), thus resulting in the photoinduced hole-electron pairs. These photoinduced electrons and holes can interact with surrounding H 2 O or O 2 molecules and generate various reactive oxygen species (ROS, such as superoxide anion radical O 2  ·− [5], hydroxyl radical OH · [6], singlet oxygen 1 O 2 [7], and hydrogen peroxide H 2 O 2 [8]), which can react with biological molecules, such as lipids, proteins, and DNA, cause their damages, and eventually kill cancer cells [1,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, recent studies have reported that the optical absorption of TiO 2 in the visible region could be improved by doping [12-14] or dye-adsorbed methods [15,16], which will facilitate the application of TiO 2 as a photosensitizer for PDT. In our previous study [10], we enhanced the visible light absorption of TiO 2 by nitrogen doping and found that the nitrogen-doped TiO 2 (N-TiO 2 ) showed much higher visible-light-induced photokilling effects on cancer cells than the pure TiO 2 .…”
Section: Introductionmentioning
confidence: 99%